FORMATION OF PROFESSIONAL FOREIGN LANGUAGE COMPETENCE FOR FUTURE LAWYERS IN THE AVIATION SPHERE - Lomakina, Maryna; Zelenska, Liliia; Kovalova, Inna (Collection of scientific papers «ΛΌГOΣ», 2025)
The article presents the process of professional foreign language competence formation for future lawyers at aviation higher education institutions. The pecularities of professional foreign language training have been analyzed, the main approaches and methods that contribute to the development of communicative skills in the sphere of aviation law have been outlined. The necessity of an interdisciplinary approach to English for Specific Purposes instruction has been substantiated within the context of the aviation sector globalization and the increasing demands for professional language competence among legal professionals.